The adoption of financial technology solutions by lower-income earners in South Africa - Manamela, Nthabiseng (University of the Witwatersrand, Johannesburg, 2023)
The aim of the study was to gain an understanding of the factors that drives financial technology (FinTech) adoption by lower-income earners in South Africa. This study focuses on the lower-income earner's behaviour with regards to the adoption of FinTech solutions. The conceptual framework for this study is drawnfrom the theoretical frameworks deployed in the study to form the research variables. Qualitative research method was used for this study. Data was collected using interviews in a semi-structured format and the data was analysed using thematic data analysis. The study found that there was a general lack of understanding of FinTech solutions. The findings showed that the most common FinTech solutions adopted were from the Banking industry, suggesting that there is a knowledge gap of the different FinTech solutions available for consumption. The study found 6 enabling factors to FinTech adoption; Trust, economic benefit, digital literacy, and brand and 4 barriers to FinTech adoption; Associated cost, perceived risks, income levels and education levels. The study concludes that addressing these factors requires a multi-pronged approach. It recommends that FinTech providers, policy makers and government adopt the enhanced FinTech adoption model to improve their understanding on the factors that enable or deter the adoption of FinTech solutions by lower income. It is further recommended that FinTech providers must accelerate marketing efforts to raise awareness of FinTech and use of a hybrid contact approach. The study emphasises the need to expedite policies and regulations that addresses high cost of mobile data. The study also urges government to play iii a role in the adoption of FinTech solutions by investing in ICT infrastructure needed to support the adoption of FinTech solutions
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Fintech adoption; Lower-Income earners; TAM; Perceived Risk Theory; South Africa; UCTD; SDG-8: Decent work and economic growth